Dilthey’s Hermeneutics in Unveiling the Locality of Tafsir Al-Mishbah - Handayani, Tri; Rusli, Ris'an; Al-Kaff, Idrus (QOF, 2026)
This article examines M. Quraish Shihab’s Tafsir Al-Mishbah through Wilhelm Dilthey’s three-stage hermeneutic framework: Erlebnis, Ausdruck, and Verstehen. Employing qualitative library research with a hermeneutic approach, this study analyzes how local cultural experiences and historical contexts are reflected in Shihab’s interpretation of the Qur’an. The analysis locates Erlebnis within Shihab’s socio-cultural background, including his Bugis-Makassar upbringing and intellectual formation, which shaped his interpretive perspective. These experiences are expressed as Ausdruck in his contextual reading of Qur’anic verses, particularly concerning sacrificial practices in QS al-Ḥajj [22]: 34–37 and communal ethics in QS al-Mā’idah [5]: 2, where local cultural symbols and social values serve as interpretive references. Through Verstehen, these cultural expressions are understood within the framework of maqāṣid al-sharī‘ah, demonstrating that local traditions may serve as meaningful resources for Qur’anic interpretation without undermining the universal principles of Islam. The study argues that Tafsir Al-Mishbah represents a contextual mode of exegesis that integrates Indonesian cultural realities into the interpretive process. This finding contributes to the development of Indonesian hermeneutic discourse and offers a model for contextual tafsir in culturally plural Muslim societies.